2004
DOI: 10.1111/j.1471-0528.2004.00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine versus placebo in the treatment of European and Canadian women with stress urinary incontinence

Abstract: Objective To assess the efficacy and safety of duloxetine in women with stress urinary incontinence.Design Randomised double-blind, placebo-controlled clinical trial.Setting Fort-six centres in seven European countries and Canada.Population Four hundred and ninety-four women aged 24-83 years identified as having predominant symptoms of stress urinary incontinence using a clinical algorithm that was 100% predictive of urodynamic stress urinary incontinence in a subgroup of 34 women. Methods The case definition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
171
2
15

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(203 citation statements)
references
References 24 publications
15
171
2
15
Order By: Relevance
“…57,117,128,[130][131][132][133][134][136][137][138][139][140][141][142][143][144][145]189 Twelve of these involved drug therapy and used a placebo to blind participants. 57,117,[136][137][138][139][140][141][142][143][144][145] In the other seven studies, participants were blinded through sham ES, [130][131][132][133][134]189 or imitation or placebo PFMT. 57,128 Six studies (6.8%) reported that health-care providers were blinded.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…57,117,128,[130][131][132][133][134][136][137][138][139][140][141][142][143][144][145]189 Twelve of these involved drug therapy and used a placebo to blind participants. 57,117,[136][137][138][139][140][141][142][143][144][145] In the other seven studies, participants were blinded through sham ES, [130][131][132][133][134]189 or imitation or placebo PFMT. 57,128 Six studies (6.8%) reported that health-care providers were blinded.…”
Section: Risk Of Bias In Included Studiesmentioning
confidence: 99%
“…This was worse than those reported in the pooled analysis from the Phase 3 randomised placebocontrolled studies on a worldwide scale, which was 75%. [6][7][8][9] Interestingly a similar number of women with mixed incontinence and USI had a PGI-I score indicating improvement. This suggests that there may be a role for duloxetine in the treatment of women with mixed incontinence.…”
Section: Discussionmentioning
confidence: 92%
“…16 Duloxetine trials suggest benefit in the treatment arm of between 49-65% and low discontinuation rates due to adverse effects (22%). [6][7][8][9] A Cochrane review reports that duloxetine significantly improved the QoL of patients with SUI. 17 The review reported that one in eight women stopped duloxetine due to adverse effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations